Korelasi Profil Lipid dengan CK-MM terhadap Resiko Kejadian Penyakit Jantung Koroner pada Penderita Hipertensi Usia Produktif - Karwiti, Witi; Lestari, Wuni Sri; Nasrazuhdy, Nasrazuhdy; Nurhayati, Nurhayati; Yusneli, Yusneli; Asrori, Asrori (Journal of Telenursing (JOTING), 2024)
This research is descriptive in nature with primary data from lipid profile and CK-MB examination results. The research method is observational with a cross sectional approach. The research sample was hypertensive patients at PKM in the city of Jambi with a sample of 50 people. The independent variable is lipid profile and the dependent variable is CK-MB. The results of the study showed that variables that had average levels above the normal value were cholesterol levels (211.43 mg/dl) where the value was normal (<200 mg/dl), as well as triglyceride levels (187.93) with normal values ​​(<150 mg .dl), while the average levels of LDL, HDL and CK-MB values ​​are still within normal limits. The conclusion of the study is that there is a significant relationship between cholesterol and triglyceride levels and CKMB enzyme activity in hypertension sufferers and there is no significant relationship between HDL and LDL levels and CKMB values ​​in hypertension sufferers. Keywords: Lipid profile, CK-MB, CHD risk, hypertension, productive age